2020 one city, seven people, and the year everything changed - Klinenberg, Eric 1970- (Alfred A. Knopf, 2024)
"Crisis has a way of laying bare our truest selves: who we trust, which principles and impulses we heed, whose lives we deem expendable. As it ravaged millions of lives, the Covid-19 pandemic revealed and accentuated the dividing lines that had already, for decades, splintered American public life. Against the backdrop of the 2020 presidential election, misinformation regimes, and the transformation of the facemask into a flagrant political symbol, acclaimed sociologist Eric Klinenberg takes careful inventory of how the U.S. and other nations handled the extraordinary challenges of that seminal year. Any autopsy searches for causes, and in this book, Klinenberg uses seven people's piercingly vivid reflections to examine how communities across the globe reckoned with the profound tragedy and loss of 2020--and how they built networks of solidarity in an attempt to survive. We move from the gross negligence in Canadian for-profit nursing homes, to England's gradualist approach to instating robust Covid safety protocols, to early policy innovations in Australia, South Korea, and Taiwan, which dramatically curtailed the virus' spread. According to Klinenberg, our capacity to bear witness to the rampant failures and successful models of resilience of 2020 will help shape our responses to the escalating climate emergency, the ongoing fight for racial justice, and widening global economic disparities. This book is both mirror and roadmap-a reflection of the social divisions that plague our world and a set of principles for how we might approach the next global catastrophe differently
Keywords: COVID-19; Ungleichheit; USA; New York, NY; History